Family Caregiving Behavior and its Correlation with Stroke Severity among Patients with Stroke - Sari, Ratna Yunita; Riska Rohmawati; Faizah, Imamatul; Dyah Ika Krisnawati; Hasina, Siti Nur; Anh, Duong Thi To; Kuo, Tsung-Rong (Universitas STRADA Indonesia, 2026)
Background: Stroke is a disease that requires intensive family care. Suboptimal family care can worsen a stroke patient's condition. Purpose: This study aimed to determine family caregiving behaviours, based on the severity of the stroke, at PHC Hospital Surabaya. Methods: The study design employed analytical observation using a cross-sectional method, with a study population of 170 respondents and a sample of 120 selected via simple purposive sampling. The independent variable in this study was family behavior, and the dependent variable was tingkat keparahan pasien stroke. The instruments used were National Institutes of Health Stroke Scale (NIHSS) Questionnaire and the Family Behaviour Questionnaire. Data analysis utilised the Spearman rank test. Results: The results of the study showed that almost half (49.2%) had adequate behavior in caring for stroke patients and nearly half (44.2%) had severe stroke severity with a value of ρ = 0.014 correlation coefficient of 1.000, which means there is a relationship between family behavior in caring for stroke patients and the severity of stroke patients at PHC Hospital Surabaya with a robust correlation. Conclusion: Family caregiving behavior is significantly associated with stroke severity. Improving education and guidance for families of stroke patients is crucial to supporting successful patient care and rehabilitation.